2008
DOI: 10.1002/da.20370
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana coping motives interact with marijuana use frequency to predict anxious arousal, panic related catastrophic thinking, and worry among current marijuana users

Abstract: The present investigation evaluated whether coping motives for marijuana use interacted with past 30-day frequency of marijuana use in relation to anxiety-relevant variables among community-recruited young adult marijuana users (n=149). As expected, after covarying cigarettes per day, alcohol use, and total years of marijuana use, the interaction between frequency of past 30-day marijuana use and coping motives predicted anxious arousal symptoms, agoraphobic cognitions, and worry. Marijuana users who demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
1
14
1
Order By: Relevance
“…For these women, marijuana use may represent a reliable method that they expect will decrease tension and anxiety. Previous studies have established an association between marijuana use and anxiety-related constructs, that is, agoraphobic cognitions, anxiety arousal, 27,43 affective liability, 28 negative affect, 29 and worry. 24 Our findings add support to this link between anxiety and marijuana use by demonstrating that TRR expectancies mediate the relationship between GAD symptoms and use in a nontreatment-seeking sample of young women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these women, marijuana use may represent a reliable method that they expect will decrease tension and anxiety. Previous studies have established an association between marijuana use and anxiety-related constructs, that is, agoraphobic cognitions, anxiety arousal, 27,43 affective liability, 28 negative affect, 29 and worry. 24 Our findings add support to this link between anxiety and marijuana use by demonstrating that TRR expectancies mediate the relationship between GAD symptoms and use in a nontreatment-seeking sample of young women.…”
Section: Discussionmentioning
confidence: 99%
“…24 In general, substance abusers frequently characterize their use as a means for coping with psychiatric symptoms. [25][26][27] Among marijuana users, coping motives have been found to be associated with a variety of anxiety-related constructs: agoraphobic cognitions, anxiety arousal, 27 affective liability, 28 negative affect, 29 and worry. 24 Little is known however, about the relationship between coping motives and GAD, the most common anxiety disorder among women.…”
Section: Marijuana Use Anxiety and Coping Expectanciesmentioning
confidence: 99%
“…In the present study, current marijuana use status was defined as responses of one or greater on this item, indicating at least low levels of use within the past 30 days. The MSHQ has been employed successfully in past research Bonn-Miller et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, several studies using the MMM have found associations between specific motives and frequency of cannabis use and cannabis dependence (Bonn-Miller & Zvolensky, 2009;Bonn-Miller, Zvolensky, Bernstein, & Stickle, 2008;Buckner, Bonn-Miller, Zvolensky, & Schmidt, 2007;Bujarski, Norberg, & Copeland, 2012;Chabrol et al, 2005;Fox, Towe, Stephens, Walker, & Roffman, 2011;Johnson, Mullin, Marshall, Bonn-Miller, & Zvolensky, 2010;Mitchell, Zvolensky, Marshall, Bonn-Miller, & Vujanovic, 2007;Simons, Correia, & Carey, 2000;Zvolensky et al, 2007). However, most of these studies were conducted in predominantly 'white' student populations and/or populations with relatively infrequent patterns of cannabis use.…”
Section: Introductionmentioning
confidence: 93%